Frequently Asked Questions about the Africanized Honey Bee in Florida - Michael K. O’Malley; James D. Ellis; Anita S. Neal (EDIS)
ENY-140, a 3-page fact sheet by M. K. O’Malley, J. D. Ellis, and A. S. Neal, provides information about Africanized honey bees (AHB) in a question-and-answer format. Published by the UF Department of Entomology and Nematology, December 2007.